2016
DOI: 10.15406/jsrt.2016.01.00009
|View full text |Cite
|
Sign up to set email alerts
|

In vitro Osteoinduction Potential of a novel Silica Coated Hydroxyapatite Bioscaffold Seeded with Rabbit Mesenchymal Stem Cell

Abstract: For CFU-F assay, 1×106 bone marrow nucleated cells per 60-mm dish were seeded and cultured at 37°C in 5% CO 2 for 12days with media change on every 2days, followed by crystal violet staining. The numbers of CFU-Fs were counted under a microscope. Quantification of osteoblasts (CFU-OB assay) For CFU-OB assay, 1×106 bone marrow nucleated cells per 60-mm dish were seeded and cultured for 21days in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
1
2
0
Order By: Relevance
“…Although calcium levels reportedly rise sharply around 15–21 days post-surgery, our study observed an increase in phosphorus levels on the 30th day. Overall, increased phosphorus levels were noted in all groups except the control, consistent with previous findings [ 28 ]. Ionized calcium levels decreased during fracture healing, likely due to long-term BMP-2 administration favoring higher bone formation.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Although calcium levels reportedly rise sharply around 15–21 days post-surgery, our study observed an increase in phosphorus levels on the 30th day. Overall, increased phosphorus levels were noted in all groups except the control, consistent with previous findings [ 28 ]. Ionized calcium levels decreased during fracture healing, likely due to long-term BMP-2 administration favoring higher bone formation.…”
Section: Discussionsupporting
confidence: 91%
“…Ionized calcium levels decreased during fracture healing, likely due to long-term BMP-2 administration favoring higher bone formation. BMP-2 lowers calcium non-significantly in a 60-day bone healing study [ 28 ]. Ionized calcium, crucial for bone formation, decreases during progressive phases of bone tissue regeneration [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation